Dynamics in Architecture in the city of Bamenda - Awah Paschal (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Studi Islam Sunan Doe, 2022)
The German penetration into the hinterlands of Cameroon brought about urban dynamics in architecture in the city of Bamenda. This study seeks to explain the mutations that have taken place in the city of Bamenda from the colonial era which is 1884 to date. Our methodology used a qualitative approach to data collection and analysis. Techniques like; in-depth interviews, focus group discussions, and photographs were explored. Our findings reveal that the inhabitants of Bamenda are copying and embracing Western models as time passes. The advent of modernity is pushing everyone to put up a self-content structure where he/she can live comfortably. Also, the old buildings are being demolished to erect new and befitting ones. The development of infrastructural projects has caused a rural exodus and there is limited land for construction, as a result of this, the inhabitants are forced to build story buildings to meet up with their construction demands hence leading to urban dynamics in architecture in the city of Bamenda. We also noticed that the culture of the Bamenda man is fast depreciating due to the introduction of modernity. The changes in architecture in the city of Bamenda have greatly improved the living conditions of the inhabitants.